ANÁLISIS SEMIÓTICO DEL POLIEDRO FUTBOLÍSTICO COMO TEXTO LITERARIO (De la Crítica, 2024)
The text proposes, from the critical analysis of the short story "El Cesped" by Mario Benedetti, to propose the construction of the semiotic polyhedron of soccer, understanding this sport as a cultural phenomenon that can be read and interpreted from semiotics, the science that studies the signs and the systems of signification. The objective is to demonstrate that the soccer polyhedron, understood as the set of elements that make up the game of soccer, can be considered a literary text that generates multiple meanings and that is inscribed in a specific culture. To achieve this, Lotman's theory of the semiosphere is used, which defines the semiotic space containing all possible signs and their combinations, and the concept of text as a complex and structured unit of signs that relate to each other and to the context.